(untitled) (Journal of the College of Education for Women, 2019)
After the tiring search in sources about this major. I agree with Cofians aboutPossibility of the subjects comes clause else it comes phrase in many position Imentioned it in evidences . there clear proof the verb comes objective of clause if ituninflected, it will come subject of the passive. else it mention in previousevidences. also genestive clause comes subject of the passive if it the subject comesuninflected with the presence the object . It is clear in the language of Roba spoetry which it is mentioned in the search and others .